PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. KARYA PLASINDO MEDAN - Rini Astuti (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2014)
The purpose of this study was to determine whether the development has an impact on the productivity of employees. Which is the object of this research is PT. Karya Plasindo Medan which is a manufacturing company that produces vacuum forming plastic bags and plastic bag and HD-PE plastic food and beverage. From the discussion conducted in this study, the positive results obtained between variables X (development) to variable Y (productivity) with the results of the correlation coefficient of 0.92. This means that there is the effect of the development on the productivity of employees at PT. Karya Plasindo Medan.